# Copyright 2013, 2009, 2005, 2002 Pearson, Education, Inc.

5.5 The Greatest Common Factor and Factoring by Grouping .

3) The product of the factors found in Steps 1 and 2 is the GCF of the monomials. . 2) Find the GCF of the variable factors. Greatest Common Factor Greatest common factor – largest quantity that is a factor of all the integers or polynomials involved. Finding the GCF of a List of Monomials 1) Find the GCF of the numerical coefficients.

12 and 8 12 = 2 · 2 · 3 8=2·2·2 So the GCF is 2 · 2 = 4. . 7 and 20 7=1·7 20 = 2 · 2 · 5 There are no common prime factors so the GCF is 1. Example Find the GCF of each list of numbers.

a. 6x5 and 4x3 6x5 = 2 · 3 · x · x · x 4x3 = 2 · 2 · x · x · x So the GCF is 2 · x · x · x = 2x3 . x3 and x7 x3 = x · x · x x7 = x · x · x · x · x · x · x So the GCF is x · x · x = x3 b. Example Find the GCF of each list of terms.

. and x4y6is x3y4. smallest exponent on x smallest exponent on y The GCF of x3y5. x6y4. Helpful Hint Remember that the GCF of a list of terms contains the smallest exponent on each common variable.

6x3 – 9x2 + 12x = 3x · 2x2 – 3x · 3x + 3x · 4 = 3x(2x2 – 3x + 4) b. 14x3y + 7x2y – 7xy = 7xy · 2x2 + 7xy · x – 7xy · 1 = 7xy(2x2 + x – 1) . a. Example Factor out the GCF in each of the following polynomials.

1) 6(x + 2) – y(x + 2) = 6(x + 2) – y(x + 2) = (x + 2)(6 – y) 2) xy(y + 1) – (y + 1) = xy (y + 1) – 1(y + 1) = (y + 1)(xy – 1) . Example Factor out the GCF in each of the following polynomials.

This will usually be followed by additional steps in the process. Factoring Remember that factoring out the GCF from the terms of a polynomial should always be the first step in factoring a polynomial. .

15 x 3  10 x 2  6 x  4 15 x 3  10 x 2  6 x  4  (15 x 3  10 x 2 )  (6 x  4)  5 x 2 (3x  2)  2(3 x  2)  (3 x  2)(5 x 2  2) . Example Factor by grouping.

Example Factor by grouping. 2a 2  5ab  2a  5b 2a  5ab  2a  5b 2  (2a 2  5ab)  (2a  5b)  a(2a  5b)  1(2a  5b)  (2a  5b)( a  1) .

x3 + 4x + x2 + 4 x3 + 4x + x2 + 4 = (x3 + 4x) + (x2 + 4) = x(x2 + 4) + 1(x2 + 4) = (x2 + 4)(x + 1) . Example Factor by grouping.

2x3 – x2 – 10x + 5 2x3 – x2 – 10x + 5 = (2x3 – x2) – (10x + 5) = x2(2x – 1) – 5(2x – 1) = (2x – 1)(x2 – 5) . Example Factor by grouping.

Example Factor by grouping. 21x3y2 – 9x2y + 14xy – 6 = (21x3y2 – 9x2y) + (14xy – 6) = 3x2y(7xy – 3) + 2(7xy – 3) = (7xy – 3)(3x2y + 2) .